Batteries for automotive use - Reasbeck, Philip (Electronic & electrical engineering research studies. Power sources technology series, 1997)
The rapid development of automotive electrical systems in recent years has renewed interest in the power sources which support the complex array of electronic controls, sensors and actuators which are taken for granted in modern road vehicles. Written by authors who are well known for their knowledge and experience of all aspects of the lead-acid battery for automotive use, this book provides a comprehensive treatise of the electrical/ electronic system requirements of the vehicle and the way in which these are satisfied by the battery.